THU0586 ESTABLISHING THE KEY COMPONENTS OF A EULAR PORTFOLIO FOR TRAINING IN RHEUMATOLOGY: A EULAR SCHOOL OF RHEUMATOLOGY INITIATIVE. (2nd June 2020) - Van Onna, M.; Ramiro, S.; Haines, C.; Holland-Fischer, M.; Da Silva, J. A. P.; Dudler, J.; Edwards, C.; Alunno, A.; Nikiphorou, E.; Falzon, L.; Sivera, F.
Abstract : Background: In clinical training, a portfolio is expected to stimulate learning and encourage critical reflection. Some, but not all, European countries use a portfolio in rheumatology training, and their scope varies widely. A EULAR portfolio for Rheumatology trainees could contribute to improve overall training, raise educational standards, foster the setting of common goals and harmonize rheumatology training across countries. Objectives: Develop key components that should be included in a EULAR portfolio of Rheumatology. Methods: A working group (WG) composed of 9 rheumatologists and 1 educationalist was established. A systematic literature review (SLR) was conducted in November 2018, according to the PIM structure: Population: trainees; Instrument of interest: portfolio; Measurement of properties of interest: content portfolio. A survey was disseminated among the WG group and WG members of the EMerging EUlar NETwork (EMEUNET), inquiring about the content and structure of existing national portfolios. Portfolio materials of selected countries were reviewed. Last, the WG elected the key components of the portfolio. Results: 13/2, 034 articles were included in the SLR (12 high/1 moderate risk of bias). Information on direct observation of procedural skills (DOPS) (9/13), personal reflections (8/13), learning goals (5/13) and multisource feedback (5/13) were most often included in the portfolio. Twenty-five respondents filled out the survey (response rate ≈ 50%). Reflective writing (n=7), learning goals (n=4) and feedback (n=4) were considered the most useful components of a portfolio. About half indicated that a portfolio was a bureaucratic burden; 4 respondents mentioned lack of feedback by supervisors as a barrier. Portfolio materials of 7 European countries were reviewed. Several portfolios (Germany, Italy, Greece and Spain) were logbooks, i.e. a record of clinical activities. Other portfolios (UK, Denmark, The Netherlands) also included information on workplace-based assessments, learning goals, and personal reflections. The proposed key components of the portfolio are included in Table 1 . Conclusion: This initiative resulted in the establishment of a list of key components to be included in a EULAR portfolio of Rheumatology. Assessment forms for each key portfolio component are currently being developed. Portfolio implementation, particularly in countries that do not use it yet, may contribute significantly to promote a higher standard of patient care across Europe. Disclosure of Interests: Marloes van Onna: None declared, Sofia Ramiro Grant/research support from: MSD, Consultant of: Abbvie, Lilly, Novartis, Sanofi Genzyme, Speakers bureau: Lilly, MSD, Novartis, Catherine Haines: None declared, M. Holland-Fischer: None declared, José Antonio P. da Silva Grant/research support from: Pfizer, Abbvie, Consultant of: Pfizer, AbbVie, Roche, Lilly, Novartis, Jean Dudler: None declared, Christopher Edwards Grant/research support from: Abbvie, Biogen, Roche, Consultant of: Abbvie, Samsung, Speakers bureau: Abbvie, BMS, Biogen, Celgene, Fresenius, Gilead, Janssen, Lilly, Mundipharma, Pfizer, MSD, Novartis, Roche, Samsung, Sanofi, UCB, Alessia Alunno: None declared, Elena Nikiphorou: None declared, L. Falzon: None declared, Francisca Sivera: None declared